Dendrochronological analysis of altarpiece, Kvæfjord 2, Norway C3216. CATS dendro report 7 - Daly, Aoife (Statens Museum for Kunst, Denmark, 2014)
In this report, the non-invasive dendrochronological analysis of the altarpiece called Kvæfjord 2, Norway, is described.